Development Digital Comic Using Pixton Based Of Model Problem Based Learning (PBL) On PPKn Material In Class VII Junior High School 10 At Serang City - Desi Ardianti; Ria Yuni Lestari; Wika Hardika Legiani (Institut Pendidikan Indonesia, 2023)
Abstrak This research was conducted to develop digital comic learning media in the subject of Pancasila and Citizenship Education which was carried out at SMP Negeri 10 Kota Serang. The purpose of developing digital comics is to help teachers in facilitating teachers in learning activities in the classroom and to attract students' attention. This research was conducted using the research and development (R&D) method using the Borg & Gall model which has been modified by Sugiono into 5 stages of development. Expert validation aims to determine the feasibility of the media carried out by two experts, namely media experts and material experts, obtaining a score of 80.00% from media experts who are categorized as feasible and obtaining a value of 81.33% from material experts who are included in the very feasible category. Trials were held to find out the responses and assessments of students which were carried out on 54 respondents who obtained a score of 83.22% which can be categorized as very feasible learning media.Keywords: Development, Digital Comic, Pancasila and Civic Education. Abstrak Penelitian ini dilakukan untuk mengembangkan media pembelajaran komik digital pada mata pelajaran Pendidikan Pancasila dan Kewarganegaraan yang dilakukan di SMP Negeri 10 Kota Serang. Tujuan dilakukan pengembangan komik digital yaitu untuk memembantu guru dalam memudahkan guru dalam kegiatan pembelajaran di dalam kelas dan untuk menarik perhatian siswa. Penelitian ini dilakukan dengan menggunakan metode penelitian dan pengembangan R&D) menggunakan model Borg & Gall yang telah dimodifikasi oleh Sugiono menjadi 5 tahap pengembangan. Validasi ahli bertujuan untuk mengetahui kelayakan media yang dilakukan oleh dua orang ahli yaitu ahli media dan ahli materi memperoleh nilai 80,00% dari ahli media yang dikategorikan layak dan memperoleh nilai 81,33% dari ahli materi yang termasuk dalam kategori sangat layak. Uji coba diadakan untuk mengetahui respon dan penilaian dari peserta didik yang dilakukan pada 54 responden yang memperoleh nilai 83,22% yang dapat dikategorikan bahwa media pembelajaran sangat layak.Kata Kunci: Pengembangan, Komik Digital, Pendidikan Pancasila dan Kewarganegaraan.",